Effects of Carbohydrates on the Hydrodeoxygenation of Lignin-Derived Phenolic Compounds - Dwiannoko, Adid Adep; Lee, Sangheon; Ham, Hyung Chul; Choi, Jae-Wook; Suh, Dong Jin; Ha, Jeong-Myeong (AMER CHEMICAL SOC, 2015)
Simulating lignocellulose-derived pyrolysis oil, the effects of carbohydrate derivatives on the hydrodeoxygenation of lignin-derived phenolic compounds, guaiacol in this study, were observed using supported ruthenium catalysts. Among several carbohydrate derivatives which possibly exist in the pyrolysis oil, the addition of furfural and 5-hydroxymethylfurfural (5-HMF) significantly decreased the conversion of guaiacol, with density functional theory (DFT) calculations indicating that guaiacol competes with furfural and 5-HMF to adsorb onto the ruthenium nanoparticle surface, thus suppressing the hydrogenation of guaiacol.
Keywords: BIO-OIL; PHASE HYDRODEOXYGENATION; CATALYTIC CONVERSION; PYROLYSIS; GUAIACOL; CARBON; FUELS; MASS